Traditions of Teacher and Student, Theoretical and Practical Harmony in Teaching Shashmakom - ugli, Orifjonov Husniddin Sohibjon (Research Parks Publishing LLC, 2023)
In this article, which shows the harmony of teacher-student traditions, the doctrine of shashmaqom, which is a professional performing direction, was passed down from generation to generation, and also examines the work that has been and is still being done. in this article.